The sh!t no one tells you : a guide to surviving your baby's first year - Dais, Dawn (Seal Press, 2013)
A humorous guide for new mothers on caring for infants offers advice on the unpleasant aspects of parenting, including birthing without drugs, handling the volumes of waste babies create, and dealing with sleep deprivation.